Price variability and the speed of adjustment to the law of one price: evidence from Slovakia - Julius Horvath; Stanislav Vidovic (Bank of Finland, Institute for Economies in Transition (BOFIT), 2004)
This paper uses a large panel data set of monthly frequency final good and service prices in thirty-eight Slovak districts over a five-year period to study price variability and the working of the law of one price.We concentrate on three issues.First, using simple statistical tools, we investigate the range of price differences across Slovak districts.Second, we measure relative price variability across cities and across products.The variability of relative prices in the same district appears to be higher than the variability of prices of the same good across different districts.We identify the factors likely to be responsible for this fact.Third, using benchmarks we investigate the speed of convergence to the absolute law of one price.While we find evidence for absolute convergence, the speed is lower than that found in US cities.The speed of convergence to the relative law of one price is considerably higher.
URN:NBN:fi:bof-201408072154
Keywords: 330